In Vitro Antidiabetic and Antioxidant Activities of Aqueous Extract from the Leaf and Fruit of Psidium guajava L. - Adelina Simamora; Lusia Paramita; Nur Azreen; Adit Widodo Santoso; Kris Herawan Timotius (The Indonesian Biomedical Journal, 2018)
BACKGROUND: The leaf and fruit of Psidium guajava L. are potential for neutraceutical beverage especially for antidiabetic drink. The aims of this study were to determine the antidiabetic activity of aqueous extract of leaf (LE) and fruit (FE) from P. guajava.METHODS: Both extracts were investigated for their inhibitory effect on α-glucosidase activity in vitro. Their antioxidant activities were measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging, ferrous ion chelating, reducing power and phosphomolybdate methods.RESULTS: The IC50 of LE, FEandacarbose as a positive control were 5.67, 428.00 and 823.99 μg/mL, respectively. The enzyme kinetic analysis indicated that LE inhibited α-glucosidase in a competitive inhibition type, similar to that of acarbose. Both extracts showed antioxidant activities, with LE showed stronger activities than FE in all methods. In DPPH method, IC50 of LE and FE were 74.77 and 843.84 μg/mL respectively, compared to 53.24 and 21.36 μg/mL for reference antioxidants butylated hydroxytoluene (BHT) and ascorbic acid (AA), respectively. In ferrous ion chelating activity, the IC50 were 147.07 and 2105.05 μg/mL for LE and FE, whereas ethylenediaminetetraacetic acid (EDTA) as a control sample was 66.50 μg/mL. In reducing power and phosphomolybdate methods, at different concentrations, the activities of LE, FE, and standard compounds showed the following order: AA > BHT > LE > FE.CONCLUSION: LE from P. guajava exhibited excellent inhibitory activity against α-glucosidase. In addition, LE had better antioxidant acivities than FE. This study can recommend the aqueous extract from P. guajava as a promising candidate for neutraceutical drink for prediabetic and diabetic patients.KEYWORDS: antioxidant, aqueous extract, α-glucosidase inhibition, guava, Psidium guajava L.